PROJECTIVISTIC MEASUREMENT OF COSMISM IN THE CONDITIONS OF GLOBALIZATION - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The history since the end of the XXth - the beginning of the XXIth century became a decisive challenge for philosophers and scientists in their predicting the future of humanity and the universe as a whole. Throughout crisis time, people always recur to «eternal values». The author focuses on the philosophical concepts of M. Fedorov and the ideas of his adherent K. Tsiolkovsky, the pioneering rocket scientist, who represent the projectivistic trend in cosmism. The aim and tasks: The aim of the article is to under-stand the projectivistic character of the philosophical ideas of M. Fedorov and K. Tsiolkovsky and to reveal their value in the context of globalization. Research methods: the author uses the comparative historical method to study the development of basic ideas of the progressivist philosophers in the context of globalization and to identify their influence on the formation of public opinion. Re-search results. In the era of globalization, the ideas of the cosmists are practically brought to life. Nowadays scientists are trying to overcome an important obstacle on the road to the realization of the idea of space exploration, having the opportunity to improve human nature with the genetic intervention. In his cosmic philosophy, K. Tsiolkovsky defended the ideas of anthropocosmism and the interrela-tionship of the elements of the cosmos; wrote about the intelligent «space animal», which is able to be in the interplanetary space with-out spacesuit. Science, changing the biochemical nature of man, would help to provide comfortable conditions for life in space. It is the very subject of study of the modern biotechnology but its goal is some different. Socio-philosophical ideas of K. Tsiolkovsky remain rele-vant too. In the future, the thinker convinced, an objective need arises for changing the social structure on a global scale by reorganizing and improving it for the sake of a common shared happiness. Potentially, these ideas could be promoted by the modern globalization. The ideological inspirer of K. Tsiolkovsky was his master N. Fedorov, who was the first to urge humanity to move from experiments in earthly laboratories to experimentation on the scale of space, since «heavenly space» would require radical changes. Discussion. Fo-cusing on the key ideas of K. Tsiolkovsky and N. Fedorov is primarily caused by the fact that in the studies of modern cosmists, man as a person retains their priority ideological value. Today, humanity has abandoned the idea of the cosmos exploiting, concentrating on the idea of co-evolution. In such conditions, the ideas and beliefs of the classical cosmists have found application in formulating the ideals and norms of space activity, as well as in assessing its prospects and consequences. Conclusion. Further space researches in terms of social progress can provide humankind with a real survival prospect and significant benefits, as N. Fedorov and K. Tsiolkovsky wrote about. Humanity will never give up the idea of space exploration; we see our future with it, hoping for salvation from global problems.